Relations between present-hedonistic and future time perspective, achievement goal-orientation and regulatory strategy use in technology-rich learning environments - Marshall, Dylan D. (Animo Repository, 2013)
This cross-sectional explanatory study examines the predictive mediational relations between time perspectives. achievement goals and regulatory strategy use in high school students in the context of technology-rich. constructivist learning environments. The study adopts Bandura's (1986) social cognitive theory as its theoretical framework for the explaining the nature of predictive relations in the between the variables. Students present-hedonistic time perspective (PHTPX)(a=.77). and future time perspective (FTP) (a=.79), were measured ,using Zimbardo and Boyd's (1999) ZTPI. The mastery-approach (MA) (a.=.80). performance approach {PA) (a.=.86), achievement goals were measured with Pintrich et al.'s (1993) MSLQ and regulatory strategy use (RSU) (a=. 7 4) with Midgley et al.'s (2000) PALS and Marshall's (2012) Tech-savvy Scale. Participants were 460 international high school students of mixed gender and ethnicity aged between 15 and 18 years. Data was analyzed using path analysis SEM and the model had good fit: GFI .909, CFI, .59 SRMR, .029 (df-=4). FTP positively predicted MA and PA(p0.05). MA and PA positively predicted RSU(p<0.05) and achievement goal orientations mediate relations between FTP and RSU